Regulating the globalisation of data: Which model works best? - Erik van der Marel (European Centre for International Political Economy (ECIPE), 2021)
Novel flows that define the future of globalizationrequire new regulatory approaches,which are likely to differ between countries.So too for regulatory approaches topersonal data.Globally, there are three different regulatorymodels for personal data: the modelapplied by the US, based on an openapproach to transfer data and processdata locally; the model developed by theEU, which is a model based on so-calledconditional transfers and processing; andfinally, the model put forward by China, aframework that lurches towards autarky.The differences in regulatory approachesreflect different economic realities, and itis important to better understand how andwhy countries regulate in the way they do– particularly in the EU and US. The EU'sregulatory approach seeks model followersamong trading partners and offersadequacy for countries following a differentmodel. Many countries apply a similarmodel and, together, they cover a big portionof global trade in data-reliant services.In contrast, the US model has fewer followersand represents a much smaller share oftrade. However, this model comes with otherbenefits as it allows firms to experimentmore than in the EU and China, leading tomore digital innovations with data and fastergrowth of new firms with a strong boostingeffect on productivity. The US model aimsto capture the benefits to prosperity thatcomes from data-based innovation.The China model is in a league of its own.It is a large economy in itself and its economicscale has served the country wellby developing many new and fast-movingdigital technologies; China thereforeshares some impulses of an experimentalapproach. Yet, this regulatory approachcomes along with great restrictions, whichinhibit the cross-border integration withother countries. The China model has thelowest number of followers and representsthe smallest share of digital services trade.China's closed economy makes it thereforemuch harder to regulate internationally.These three blocs have chosen regulatorymodels that reflect their institutionalstructures and economic opportunities.Hence, there may not be one model thatfits every type of economy: there is rathera path dependence in the way regulationsare developed.However, it is important to acknowledgethat the different regulatory structures willproduce different economic outcomes.The US model will generate a lot of innovation-led growth – but not necessarily alot of innovation-driven trade. Europeanoutcomes are the opposite: the regulatorystructure doesn't produce as muchSchumpeterian growth, but it encouragestrade and Smithian growth.
Keywords: 330